Application of fractal theory to estimation of equivalent diameters of airborne carbon nanotube and nanofiber agglomerates. Issue 5 (4th May 2018) - Ku, Bon Ki; Kulkarni, Pramod
ABSTRACT: Understanding transport characteristics of airborne nanotubes and nanofibers is important for assessing their fate in the respiratory system. Typically, diffusion and aerodynamic diameters capture key deposition mechanisms of near-spherical particles such as diffusion and impaction in the submicrometer size range. For nonspherical particles with high aspect ratios, such as aerosolized carbon nanotubes, these diameters can vary widely, requiring their independent measurement. The objective of this study was to develop an approach to provide approximate estimates of aerodynamic- and diffusion-equivalent diameters of airborne carbon nanotubes (CNTs) and carbon nanofibers (CNFs) using their morphological characteristics obtained from electron micrographs. The as-received CNT and CNF materials were aerosolized using different techniques such as dry dispersion and nebulization. Mobility and aerodynamic diameters of test aerosol were directly deduced from tandem measurement of particle mobility and mass. The same test aerosol was mobility-classified and subsequently collected on a microscopy grid for transmission electron microscopy (TEM) analysis. TEM micrographs were used to obtain projected area, maximum projected length, and two-dimensional (2-D) radius of gyration of test particles. Estimates of the aerodynamic diameter and the diffusion diameter were obtained by applying the fractal theory developed for aerosol agglomerates of primary spherical particles. After accounting for the particle dynamic shape factor, estimated aerodynamic diameters agreed with those from the direct measurements (using tandem mobility-mass technique) within 30–40% for the agglomerates with relatively open structures while the diffusion diameters agreed within 40–50%. The uncertainty of these estimates mainly depends on degree of overlapping structures in the microscopy image and nonuniformity in tube diameter. The approach could be useful in calculating approximate airborne properties from microscopy images of CNT and CNF agglomerates with relatively open structures. This article not subject to US copyright law